Detection of Biofilm production in microorganisms complicating Chronic wound infections - Dr. V. Abarna; Dr. N. Sri Sakthipriya; Dr. M. Anitha Raj; Dr. E. Arthi; Dr. Bagyalakshmi; Dr. Jayalakshmi G (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: The presence of biofilm facilitates the development of infections by compromising the immune system of the patient and by contributing to the failure of antibiotic therapy, which may result in recurrent infections and the emergence of multidrug resistant pathogens. Objectives: The objective of this study is to determine the biofilm forming ability of the microorganisms infecting chronic wounds and to correlate the drug resistance with biofilm formation. Material and Methods: Wound swabs were collected from 50 patients with non-healing ulcers. Microorganisms isolated by standard microbiological techniques were screened for biofilm production by tissue culture plate method. Antibiotic sensitivity tests were done for appropriate panel of antibiotics by Kirby Bauer disc diffusion test. Results: All the 50 samples were culture positive. The most common organism isolated was Staphylococcus aureus, CoNS, Enterococcus faecalis, Beta hemolytic Streptococci, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumonia, Acinetobacter and Proteus vulgaris. Biofilm formation was determined by Tissue Culture Plate method in 63 identified isolates (39 in monomicrobial & 24 in polymicrobial infections) and 38 (60.32 %) isolates were positive for biofilm production. Most of the isolates in polymicrobial infections were strong biofilm producers. Biofilm producers were found to be more resistant to almost all the groups of antibiotics. Conclusion: If we understand the wound’s microbial flora, it allows us to manage and treat the wound better. New strategies targeting biofilm disruption or prevention of biofilm formation are important new approaches in the management of chronic wounds.